Interview with Klaus Vieweg about the Carové’s Notebooks Manuscripts - Rodrigues Raposo, Reginaldo; Rigo, Antonio (Revista Eletrônica Estudos Hegelianos, 2024)
The section consists in an interview with Klaus Vieweg (Friedrich-Schiller-Universität Jena) about his recent discovery of manuscripts attributed to Hegel’s former student, Friedrich Wilhelm Carové, containing documentation of the philosopher’s courses at the University of Heidelberg, between 1816-1818. The professor details the nature of the material, its index of authenticity, talks about the discovery itself, and reveals the minutia of a project for a critical edition of the material, considering its potential relevance and impact on research on Hegel. Vieweg also discusses issues concerning the contemporary debate around the philosopher’s corpus, and provides information collected after the first examinations.
Keywords: Carové; Hegel; Hegels Vorlesungen in Heidelberg; Klaus Vieweg